Analysis of BOP PAUD Program Effectiveness in Tanjungpinang: Challenges and Solutions in The Archipelago 2025/2026 - Rezty Pratiwi Palestina; D. Darmanto; Heri Wahyudi (Manunggal Halim Jaya, 2026)
This study aims to analyze the effectiveness of the Early Childhood Education Implementation Operational Assistance Program (BOP PAUD) in Tanjungpinang as a public policy instrument in supporting the governance and quality of early childhood education services. This research is motivated by the fact that there are still gaps between digital-based policy design and implementation practices in the field, such as delays reporting administrative errors, and limited human resource capacity in the management of BOP PAUD funds. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of the Education Office, the head of PAUD, operators, and treasurers. The research analysis uses indicators of program effectiveness according to Sutrisno, which include program understanding, accuracy of targets, timeliness, achievement of goals, and real changes. The results of the study show that the BOP PAUD Program has helped support the operations of educational units and improve financial administration governance, but the effectiveness of the program has not been optimal. The main problems are found in the low technical understanding of implementers, delays in reporting, the phenomenon of double workload, and the uneven impact of improving the quality of education services. This research confirms that the effectiveness of programs is not only determined by regulations and digital systems, but is also influenced by human resource capacity, institutional support, and coordination between policy actors. Therefore, it is necessary to strengthen the capacity of implementers, optimize technical assistance, and improve program governance based on regional needs to increase the effectiveness of the management of BOP PAUD funds.